Guided Play Sebagai Pendekatan Pedagogis Dalam Menjembatani STPPA Dan Capaian Pembelajaran PAUD (Studi Kasus Di RA Al-Istiqomah Kecamatan Cibeber Kabupaten Cianjur) - Asri Widianti; Eva Manfaatin Kartadinata; Ika Rustika Zainah (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
Play is a central learning medium in early childhood education, yet classroom practice often turns play into a teacher-controlled activity that limits children’s choices and social exploration. This study aims to describe guided play as a pedagogical approach that connects child development standards with early childhood learning outcomes at RA Al-Istiqomah, Cibeber District, Cianjur Regency. This research used a qualitative case study approach. Data were collected through classroom observation, interviews with the teacher and school principal, and learning documentation. The findings show that guided play was implemented through planning, classroom practice, and evaluation. The teacher selected learning outcomes, identified relevant child development aspects, and designed play activities such as block puzzles and collaborative play. During play, the teacher acted as a facilitator by preparing the environment, setting rules with children, asking guiding questions, providing scaffolding, and reinforcing positive behavior. Guided play supported children’s prosocial development, especially sharing, taking turns, helping peers, showing empathy, and cooperating. The study concludes that guided play can help teachers translate curriculum documents into meaningful play experiences while supporting children’s social-emotional growth.